Periodismo digital y su influencia en la formación profesional de los periodistas del cantón Quevedo, año 2022 - Moran Vera, Karen Alexandra (2022)
Digital journalism has multiple advantages, compared to traditional journalism, these advantages must be taken advantage of by professionals in the communication area in their working lives, developing efficient journalism, promoting their abilities to investigate, produce and, above all, disseminate journalistic content, giving priority to informative content more than the technological tools it has, so that it can publish, correct and expand the information it shows through the different digital platforms on its own. The objective of this research is to determine digital journalism and its influence on the professional training of journalists in the Quevedo canton. For the investigative development, the interview technique was applied to journalism professionals, elaborating a questionnaire of clear questions to be answered immediately, concluding that some of the professionals find it difficult to use the digital parameters, which are hypertextuality, which are the links that are made to other internal or external content to other additional content, they also have difficulties with the multimediality that is the publication of content, so it is necessary that they be trained for the new challenges.